Access to medicines in Turkey: Evaluation of the process of medicines brought from abroad. (24th December 2020) - Atikeler, Enver Kağan; Leufkens, H.G.M. (Bert); Goettsch, Wim
Abstract: Objective: Turkey's health reforms started in 2003 with providing changes in regulatory, financing, and healthcare services. Access to health care and pharmaceuticals increased rapidly, and this resulted with an increase in public pharmaceutical expenditures. Our study aims to quantify and to evaluate the impact of a specific process within the Turkish system called "Medicines Brought From Abroad" (MBFA). Methods: We reviewed the general reimbursement legislations of Social Security Institution (SSI), the guideline on MBFA, the SSI reimbursement list, the list of MBFA published by the Ministry of Health to describe the current supply mechanism of medicines and, in particular, the role of MBFA. Results: Total costs of the of MBFA medicines over the period 2011–17 went up to more than $520 million, which takes 7.5 percent of total public pharmaceutical expenditure for 2017. Our results showed that MBFA provides access to many orphan drugs and in total, forty-two orphan drugs listed in MBFA accounted for 83 percent of all MBFA budget in the year 2017. Nine of the top ten MBFA medicines were orphan drugs and total costs were $408 million. The highest budget impact was for eculizumab for "paroxysmal nocturnal hemoglobinuria" (PNH), covering 31 percent of total MBFA costs and 2.3 percent of overall drug costs in 2017. Conclusions: Turkey faced significant challenges for creating an access pathway for innovative medicines while continuing the sustainability of the public pharmaceutical budget like many other countries. Therefore, it may be argued that Turkey needs to create an independent health technology assessment organization to provide sustainable access to medicines in the future.